Roles and thresholds of viscosity and interfacial tension in surfactant flooding for residual oil recovery - Wang, Jiangtao; Hu, Yingxue; Chu, Xiaoyue; Sun, Gangzheng; Lu, Tao (Frontiers in Chemistry, 2025)
Surfactant flooding is an effective chemical enhanced oil recovery (EOR) technique, but the quantitative roles of viscosity and interfacial tension (IFT) in residual oil mobilization remain unclear. In this study, the physicochemical properties of surfactant solutions were first characterized by systematic measurements of viscosity and IFT, and the dynamic mechanisms of water flooding and surfactant flooding were further investigated using a pore–throat model, consisting of channels with and without pore-like structures, combined with direct numerical simulations to identify viscosity and IFT thresholds under different wettability conditions. The results show that residual oil distribution is strongly influenced by wettability: in strongly water-wet and neutral-wet conditions, oil remains as droplet- or cluster-like ganglia within pore spaces, whereas in strongly oil-wet conditions it persists as continuous wall-adhered films that are more stable and difficult to mobilize. Mechanistic analysis further indicates that the controlling parameters of mobilization differ across wettability states, reflecting the interplay between pore geometry, wettability, and interfacial forces. Based on phase diagrams constructed from simulation results, distinct regulation strategies were formulated for different wettability conditions: reducing IFT is most effective in strongly water-wet systems, a combined effect of viscosity enhancement and IFT reduction is required in neutral-wet systems, and achieving ultra-low IFT is essential in strongly oil-wet systems. Collectively, this work establishes viscosity and IFT thresholds as quantitative design criteria for surfactant flooding, providing both mechanistic understanding and practical guidance for surfactant formulation and injection optimization in chemical EOR.